Pembelajaran dengan Proyek: Mengembangkan Kemampuan Refleksi Diri dan Kolaborasi Mahasiswa Melalui Team-Based Project : research - Suci Nurpratiwi; Amaliyah Amaliyah; Nada Arina Romli (Universitas Negeri Jakarta, 2022)
This study aims to analyze the development of self-reflection and collaboration skills of students through the implementation of a team-based project model in learning for micro-teaching courses. The research was conducted at the State University of Jakarta, with the research subjects were 41 students. Data collection techniques through observation, documentation, interviews, and self-reflection questionnaires. The results showed that 72.1% of students always evaluate their performance and try to do better in teaching practice based on self-reflection results. The aspect that needs to be improved is speaking skills in front of the class (public speaking). Meanwhile, student collaboration skills have shown to be good, as indicated by the synergy in identifying, researching, analyzing, and formulating answers and solutions to the problems found and stated in the project report.